ETIOLOGY AND OUTCOME OF CONGESTIVE HEART FAILURE IN CHILDREN IN A TERTIARY CARE HOSPITAL OF JHARKHAND: A CROSS-SECTIONAL STUDY. - Anand, Chhitiz; Mahli, Rajiv Kumar; Kumar, Anil (Student’s Journal of Health Research Africa, 2024)
Background Congestive heart failure (CHF) is an important, growing public health problem causing substantial morbidity and mortality in pediatric patients. The causes vary between developed and developing countries, age, and geographical location. Congenital heart diseases and cardiomyopathy are the most common offenders in developed countries, while infections and anemia are more common in developing areas. Objective To determine the etiology and outcome of Congestive heart failure in the Department of Paediatrics, SBMC, Hazaribagh. Methods This descriptive, cross-sectional retrospective study involved 82 children diagnosed with CHF. Comprehensive data collection included history taking, physical examinations, and diagnostic tests such as CBC, chest X-rays, and echocardiograms. Statistical analyses were conducted using descriptive statistics to outline the frequency and percentage of various causes and outcomes of CHF. Results The study found that 87.8% of heart failure cases were due to cardiac causes with congenital heart diseases being predominant (74%). The most common congenital causes were ventricular septal defect (25.6%), patent ductus arteriosus (14.6%), and dilated cardiomyopathy (11%). Non-cardiac causes accounted for 12.2% of cases. The mortality rate during the study period was 14.7%. Conclusion Congenital heart diseases are the leading cause of CHF in children in this region, with a significant mortality rate. The variability of etiological factors, including both cardiac and non-cardiac causes, underscores the complex nature of pediatric heart failure management. Recommendations Future research should focus on longitudinal studies to track the long-term outcomes of pediatric heart failure and the effectiveness of various treatments across different regions and socioeconomic conditions. There is also a need for targeted public health interventions to address preventable causes of heart failure in children.